2016
DOI: 10.1590/0047-2085000000113
|View full text |Cite
|
Sign up to set email alerts
|

Personality disorder and substance related disorders: a six-month follow-up study with a Brazilian sample

Abstract: Objectives: A few Brazilian researches correlate personality disorders (PD) and substance related disorders (SRD). The aim of the present study is to investigate the association between them, to evaluate the PD frequency among chemical dependents inpatients, this comorbidity association with social and demographic characteristics, used drug of choice, its impact on clinical evolution until the moment of their committal, the frequency of relapse, self-help group -and psychotherapic adherence among SRD patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…In addition to personality traits, studies show a relation between the history of substance use and the presence of risk and impulsive behaviors, a crucial role in many psychopathological conditions, such as mood disorders, personality disorders, and developmental disorders (Jakubczyk & Wojnar, 2018;Landa et al, 2005). Krieger et al (2016), for example, identified that 55% of patients admitted for treatment due to substance use disorder were also diagnosed with personality disorder. Additionally, personality disorders and addictions are associated with an increased risk of committing crimes (Flórez et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to personality traits, studies show a relation between the history of substance use and the presence of risk and impulsive behaviors, a crucial role in many psychopathological conditions, such as mood disorders, personality disorders, and developmental disorders (Jakubczyk & Wojnar, 2018;Landa et al, 2005). Krieger et al (2016), for example, identified that 55% of patients admitted for treatment due to substance use disorder were also diagnosed with personality disorder. Additionally, personality disorders and addictions are associated with an increased risk of committing crimes (Flórez et al, 2019).…”
Section: Introductionmentioning
confidence: 99%